Hubungan Pengetahuan dan Sikap terhadap Kejadian Keputihan pada Remaja - Oktaviani, Meli; Achyar, Khamidah; Kusuma, Inggar Ratna (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Leucorrhoea is an unusual discharge other than blood from the vaginal canal, whether smelly or not, and accompanied by local itching. Leucorrhoea in adolescents can be caused by poor genital care. Lack of knowledge and attitudes in protecting the female area causes vaginal discharge. Efforts to improve health can be done through health education. This type of research uses a literature study or literature review with a descriptive research method. This study uses 2 databases: PubMed and Google Scholar. The search strategy method for obtaining journals uses the keywords